Forms of State Aid and the Importance of its Regulation - Holzerová, Patrícia; Čičková, Zuzana (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The direction of the company's operation and success in the market are related to number of strategic decisions from the moment of entering the market. One of the most important topics that companies have to deal with is financing business activities, which is not always easy and sometimes they have to reach for possible forms of help. These are mostly state aid and subsidies, effective tools that not only serve the beneficiaries by influencing their market presence and enabling to increase their competitiveness, but at the same time, they are effective for the provider, as they allow it to enter the market developments in accordance with its stated aims and intensions. However, this can lead to distortions of competition, for example by favoring certain companies, regions or types of services and goods. The presence of coordinators and regulatory authorities monitoring the use of such measures for the benefit of businesses within established criteria is therefore very important. In Slovakia this competence falls to the Antimonopoly Office of the Slovak Republic. Our paper focuses on topic of state aid in individual areas of the economy with regard to its control and regulation, which is one of the tools of competition policy.